Can complex gender issues be translated into enabling policies for women? - MacMillan, Susan (International Livestock Research Institute, 2011)
Susan Macmillan indicated that if we do not manage to find ways to place our understanding of gender issues in the context of environment, economy, agriculture, education and health, our well-meaning research might end up doing more harm than good. While gender is now on the agenda of every government and every big development project in the world, we don’t yet know what policies manage to empower women or how to implement them.